On local limit values of subharmonic and holomorphic functions - Bondar, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We prove theorems analogous to the local maximum principle and theorems on relation between limit sets, which can be used for studying singular sets.